Education of Art as a Process of Innovative and Creative Cultural Heritage in the Indonesian Society - Adisasmito, Nuning Damayanti (EDUCARE, 2008)
ABSTRACT: Transfer of culture from one generation to the next generation takes place in every period. This is an educational process in which knowledge was inherited to several groups of society within one particular country. The knowledge then becomes cultural heritage that will be used by the society. Indonesian art education is divided into traditional art education and modern art education. Despite the differences between the two, the transfer of Indonesian cultureâs values occurs in both processes. In general, art education is a processing media of cultural heritage in the context of individual development towards a socially and culturally whole human being, since art develops creativity and sensitivity for different, ever-changing aspects of life, such as the culture and the changes within the society. Art education is considered as a process of cultural inheritance and human development â a creative process that functions as an agent of change for culture.KEY WORDS: cultural heritage, educational process, art education, and transfer of Indonesian cultureâs values.About the Author: Dr. Nuning Damayanti Adisasmito is a lecturer at the Faculty of Fine Art and Design, Institut Teknologi Bandung (ITB), Indonesia. She can be contacted at: aryasena@bdg.centrin.net.idHow to cite this article? Adisasmito, Nuning Damayanti. (2008). âEducation of Art as a Process of Innovative and Creative Cultural Heritage in the Indonesian Societyâ in EDUCARE: International Journal for Educational Studies, Vol.1(1) August, pp.81-90. Bandung, Indonesia: Minda Masagi Press owned by ASPENSI in Bandung, West Java; and FKIP UMP in Purwokerto, Central Java, ISSN 1979-7877. Chronicle of the article: Accepted (June 1, 2008); Revised (July 2, 2008); and Published (August 17, 2008).